Long Term Care Nurses’ Feelings on Communication, Teamwork and Stress in Long Term Care - Fuqua, Ronald M. (Archives of Business Research, 2016)
ABSTRACT The goals of this study were to identify how long term care nursing employees felt about communication, teamwork and stress in doing their work. Data from long term care nursing employees on their comparative opinions of receiving information and being asked for their input, giving help to others and receiving help in doing their jobs, and their opinions of the stress level in their jobs were collected through an online survey. Analysis provides an assessment of associations between demographic information and nursing employees’ opinions. Results include statistically significant associations, using Pearson correlations. The differences between being told what they needed to know and being asked for their input, as well as the opinions about giving as opposed to receiving help from others and the level of stress in their jobs were found meaningful. Implications from these data include value and contribution in implementing health care management curriculum delivery based upon long term care nursing employees’ perceptions. KEY WORDS: Communication, Teamwork, Stress, Long term care, Nursing